Oprør i menigheden: Folkelig påvirkning ved besættelse af præsteembedet i Hals (Kjær Herred) - Hansen, C. Rise (Kirkehistoriske Samlinger, 1994)
In the Danish Basic Constitution (Grundloven) of 1849 it was laid down that the Constitution of the Established Church in Denmark was to be specified in detail in a special constitution. This was never fulfilled but the question of introducing a bill giving parochial church councils the power to appoint their own clergy was sometimes discussed. With a later change in Parliament in 1901, the bill introduced that year gave the authority mentioned above, and this became law in 1903. In 1900 it was necessary for a rector to be appointed in the Parish of Hals (Kjær district). The Minister of Ecclesiastical Affairs was not obliged to consult the parishioners, but, nevertheless the parishioners presented a petition with 237 signatures, pleading that they should be consulted, and believed that the intention of appointing a fanatical clergyman of the Danish Home Mission should not be followed up. The Minister at the time happened to be the rural dean for the area which included Hals Parish. He undoubtedly knew and respected some of the appeal signatories. He followed their advice and appointed a clergyman belonging to the Grundtvigianism. He was unmarried and a keen sportsman who established himself in the rectory with a female housekeeper and some hunting dogs. He was there until 1912 when he married and soon left his parish at Hals for the parishes of Boddum and Ydby (District of Thy). He retired on pension in 1938, died 1947. The petition of the inhabitants of the parish of Hals thus in fact anticipated the Act of 1903.